In situ cultivation of previously uncultivable microorganisms using the ichip - Berdy, Brittany; Spoering, Amy L; Ling, Losee L; Epstein, Slava S (Nature protocols, 2017)
This protocol details the construction and use of the ichip, a platform developed to isolate previously uncultivable microorganisms from a range of environmental samples, by enabling exposure to natural growth factors through in situ culture. Most microbial species remain uncultivated, and modifying artificial nutrient media brings only an incremental increase in cultivability. We reasoned that an alternative way to cultivate species with unknown requirements is to use naturally occurring combinations of growth factors. To achieve this, we moved cultivation into the microbes' natural habitat by placing cells taken from varying environmental samples into diffusion chambers, which are then returned to nature for incubation. By miniaturizing the chambers and placing only one to several cells into each chamber, we can grow and isolate microorganisms in axenic culture in one step. We call this cultivation platform the 'isolation chip', or 'ichip'. This platform has been shown to increase microbial recovery from 5- to 300-fold, depending on the study. Furthermore, it provides access to a unique set of microbes that are inaccessible by standard cultivation. Here we provide a simple protocol for building and applying ichips for environmental cultivation of soil bacteria as an example; the protocol consists of (i) preparing the ichip; (ii) collecting an environmental sample; (iii) serially diluting cells and loading them into the ichip; (iv) returning the ichip to the environment for incubation; (v) retrieving the ichip and harvesting grown material; and (vi) domestication of the ichip-derived colonies for growth in the laboratory. The ichip's full assembly and deployment is a relatively simple procedure that, with experience, takes ∼2–3 h. After in situ incubation, retrieval of the ichip and processing of its contents will take ∼1–4 h, depending on which specific procedures are used.